Workspirit 11 : Nederlandstalige editie (s.l. : Vitra, 2008)
Bouroullec, Ronan ; Bouroullec, Erwan ; Citterio, Antonio ; Levy, Arik ; Meda, Alberto ; Morrison, Jasper ; Gehry, Frank ; Jongerius, Hella ; Nelson, George ; Eames, Charles ; Eames, Ray ; Bey, Jurgen
Orgatec 2008, Keulen, 21-25 oktober 2008
boek
Keywords: Vitra